If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12n + 6 = 4(4n + 2) Reorder the terms: 6 + 12n = 4(4n + 2) Reorder the terms: 6 + 12n = 4(2 + 4n) 6 + 12n = (2 * 4 + 4n * 4) 6 + 12n = (8 + 16n) Solving 6 + 12n = 8 + 16n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-16n' to each side of the equation. 6 + 12n + -16n = 8 + 16n + -16n Combine like terms: 12n + -16n = -4n 6 + -4n = 8 + 16n + -16n Combine like terms: 16n + -16n = 0 6 + -4n = 8 + 0 6 + -4n = 8 Add '-6' to each side of the equation. 6 + -6 + -4n = 8 + -6 Combine like terms: 6 + -6 = 0 0 + -4n = 8 + -6 -4n = 8 + -6 Combine like terms: 8 + -6 = 2 -4n = 2 Divide each side by '-4'. n = -0.5 Simplifying n = -0.5
| 50-26= | | 2f+14= | | 42x+126=256 | | 1.6=(-1.5) | | 11x+6yi=33+6i | | 3(-6)+y=-2 | | 26-50= | | F(12)=4x+5 | | X+6y=42 | | 3p+4(0)=375 | | 4x+3(-2-3x)=24 | | 2+85m=685 | | 5=8x-8x | | 2x^2+3-6=0 | | 2+85=685 | | 4.5v-7.5v+5=-1.5 | | 6(x-6)-8=36 | | 4h-6= | | 6(x-6)-8=66 | | 2-(y+2)=-3y | | 4+2a=-6 | | 6(x-6)-8=56 | | x(x^2-5x-6x+30)=0 | | X+5.5=2 | | 2523=k-216 | | 5xblank=95 | | 4(w-6)+2w=12 | | 3(0)+4b=375 | | 11y-42x+3x-15y= | | h-41=79 | | 12x+14=98 | | -2x+6x=4(x-5) |